2014
DOI: 10.1371/journal.pone.0099892
|View full text |Cite
|
Sign up to set email alerts
|

Expression of DISC1-Interactome Members Correlates with Cognitive Phenotypes Related to Schizophrenia

Abstract: Cognitive dysfunction is central to the schizophrenia phenotype. Genetic and functional studies have implicated Disrupted-in-Schizophrenia 1 (DISC1), a leading candidate gene for schizophrenia and related psychiatric conditions, in cognitive function. Altered expression of DISC1 and DISC1-interactors has been identified in schizophrenia. Dysregulated expression of DISC1-interactome genes might, therefore, contribute to schizophrenia susceptibility via disruption of molecular systems required for normal cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Third, the DISC1-gene is a complex because there are haplotypes on this gene, including the Ser704Cys SNP, influencing brain structure and activation during memory and executive processing (Callicott et al, 2005;Palo et al, 2007). In addition, DISC1 interacts with other proteins and therefore other genes influence the effects of the DISC1-gene on cognitive functioning (Duff et al, 2013;Rampino et al, 2014). These effects could pose challenges to accurately model the effect of the Ser704Cys SNP.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Third, the DISC1-gene is a complex because there are haplotypes on this gene, including the Ser704Cys SNP, influencing brain structure and activation during memory and executive processing (Callicott et al, 2005;Palo et al, 2007). In addition, DISC1 interacts with other proteins and therefore other genes influence the effects of the DISC1-gene on cognitive functioning (Duff et al, 2013;Rampino et al, 2014). These effects could pose challenges to accurately model the effect of the Ser704Cys SNP.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…DISC1 was co segregates with major psychiatric illness in a great Scottish pedigree, Finnish cohort and Taiwanese families [4]. The DISC1 protein in interaction with number of proteins regulates several cellular functions and molecular pathways, including neuronal migration (LIS1, NDE1, NDEL1, Dixdc1), axonal bundling and elongation (FEZ1), neural progenitor proliferation (GSK3β), cell cycle regulation (PCM1), neuronal signaling (Girdin, GSK3β, PDE4), and signal transduction (Kal7, TNIK, AKAP9) [7]. Mouse models indicate the role of DISC1 protein in neurodevelopment of several brain regions, such as olfactory bulb, cortex, hippocampus, hypothalamus, cerebellum and brain stem and morphological development of adult-born granule neurons [4,8].…”
Section: Introductionmentioning
confidence: 99%
“…Mouse models indicate the role of DISC1 protein in neurodevelopment of several brain regions, such as olfactory bulb, cortex, hippocampus, hypothalamus, cerebellum and brain stem and morphological development of adult-born granule neurons [4,8]. In human peripheral blood few studies were conducted and down expression of DISC1 genes and some of the DISC1-interactome genes such as NDEL1 has been reported in schizophrenic subjects compared to non-psychiatric controls [7]. Cytoarchitectual alteration in the hippocampus is a neuropathological marker for schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…This rare variant shows significant co-segregation with schizophrenia, bipolar disorder and depression in a large family [16]. Recent studies have also shown that variation is DISC1 is also associated with other psychiatric phenotypes such as cognitive dysfunction and drug abuse [17,18,19,20]. Findings of linkage from individual pedigrees are few.…”
Section: Introductionmentioning
confidence: 99%